2017
DOI: 10.20998/2074-272x.2017.6.07
|View full text |Cite
|
Sign up to set email alerts
|

NUMERICAL SIMULATION OF THERMAL BEHAVIOR AND OPTIMIZATION OF a-Si/a-Si/C-Si/a-Si/A-Si HIT SOLAR CELL AT HIGH TEMPERATURES

Abstract: Цель. Кремниевые гетероструктурные солнечные элементы, в частности гетеропереходы с ячейками внутреннего тонкого слоя (HIT), в последнее время рекомендуются для использования в качестве кремниевых элементов, поскольку они легко изготавливаются при низкой температуре обработки и имеют высокую оптическую и температурную стабильность, а также более высокий к.п.д., чем солнечные элементы на основе гомоперехода. В настоящей работе впервые предлагается относительно точная вычислительная модель для более точного расч… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…Recent simulation and experimental studies of temperature effects on the SHJ solar cell performance showed that efficiency is deteriorated at both temperatures below and above the STC temperature (25 °C) [11,[16][17][18][19][20]. At low temperatures the reduction of efficiency was mostly attributed to lowering of the FF, due to the ITO/a-Si:H heterojunction (and their work function mismatch) [16,18], whereas at temperatures above STC it was attributed to lowering of the VOC [11,20].…”
Section: Introductionmentioning
confidence: 99%
“…Recent simulation and experimental studies of temperature effects on the SHJ solar cell performance showed that efficiency is deteriorated at both temperatures below and above the STC temperature (25 °C) [11,[16][17][18][19][20]. At low temperatures the reduction of efficiency was mostly attributed to lowering of the FF, due to the ITO/a-Si:H heterojunction (and their work function mismatch) [16,18], whereas at temperatures above STC it was attributed to lowering of the VOC [11,20].…”
Section: Introductionmentioning
confidence: 99%
“…Зазначена методика є технологічно простою і економічною, а завдяки підбору чи синтезу відповідного класу люмінофорівможливо забезпечити необхідний рівень екологічності виробництва і експлуатації відповідного класу сонячних елементів. Аналіз наукових публікацій, що було проведено у рамках даного дослідження, включав у себе аналіз сучасних методів впровадження концепції «Зеленої енергетики» [1-3] та, зокрема, сонячної енергетики [4][5][6][7][8]. Також було визначено, класи фотолюмінесцентних барвників та особливості їх синтезу, що можуть бути використані для оптимізації роботи сонячних елементів шляхом стоксового зсуву сонячного випромінювання [9][10][11].Проведений аналіз вказав на відсутність цілісної методологічної бази, яка може надати можливість визначити оптимальну конструкцію сонячного елементу на сонові кремнієвої підкладки з фотолюмінесцентним покриттям.…”
unclassified